Economic Analysis of a NO Centrifugal Sugarcane (panela) and Bioethanol Production Plant Located in Villeta Cundinamarca, Colombia - Dionisio Malagon-Romero; Nazly Dayanna Leon Caballero; Jorge Rene Silva; Harvey A. Milquez-Sanabria (Chemical Engineering Transactions)
The energy sector remains globally concerned about the escalating energy demand driven by swift population growth and industrial progress. Biomass plays a fundamental role in this transition because it is composed of biodegradable organic matter that contributes to the reduction in environmental impact. Among the various sources of biomass for biofuel production is sugarcane (Saccharum officinarum), which, in addition to being used to produce sweeteners such as sugar and panela, stands out as one of the main raw materials for bioethanol production. The fermentation of sugarcane juice with the yeast Sacharomyses cerevisiae, one of the most studied microorganisms for bioethanol production. Furthermore, the Department of Cundinamarca is the municipality of Villeta, known as Panela city, for its extensive cultivation of sugarcane to produce Panela. In this region, traditional methods are used to produce panela, which leads to the generation of tons of carbon dioxide. In addition, compared with the sugar industry, panela production processes, which are artisanal, present a great disadvantage. This project presents a feasible alternative for sugarcane production processes to be carried out in a more efficient way and with energy and therefore economic gains, using ASPEN PLUS. With a feed rate of 1,000 kg/h of sugarcane, a production rate of 20 kg/h of anhydrous ethanol was obtained: 60.32 kg/h of char, 103.29 kg/h of noncondensable gases, and 113.21 kg/h of bio-oil. The economic analysis evaluated obtaining income represented by a net present value of $US$ 2´155,076; in addition, it has a profitability of 29%, which is above the internal rate of opportunity established at 20%.